Metode PCQ dan Queue Tree untuk Implementasi Manajemen Bandwidth Berbasis Mikrotik - April Firman Daru; Febrian Wahyu Christanto; Arif Kurniawan (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Bandwidth problems are the most frequently encountered problems in sharing information traffic or internet access on computer networks. The factor that causes slow internet access is the large number of devices connected to the internet that are not matched by the availability of sufficient bandwidth and the lack of available bandwidth. This can be accommodated with bandwidth management methods. Bandwidth management in Mikotik uses several bandwidth sharing methods such as PCQ (Per Connection Queue), Queue Tree, and HTB (Hierchichal Token Bucket). This research uses 2 (two) bandwidth management methods, namely PCQ and Queue Tree because these methods can divide bandwidth automatically according to the number of active users and are more effective in sharing bandwidth based on Mikrotik. PCQ is a method aimed at optimizing QoS for large-scale internet networks where all queues are the same for all sub-streams, while Queue Tree is a method designed to carry out more complex queuing tasks for network traffic. The purpose of this research is to optimize the limited internet bandwidth so that it can be accessed by all users in the Local Area Network and automate the queue of devices connected to the network according to user needs so as to produce a more stable computer network performance using the network development method, namely NDLC. The results of the tests were carried out 10 times using a bandwidth of 10 Mbps which resulted in an average jitter of 1.64 ms, ping 36.8 ms, 2 Mbps throughput, and 0.1% packet loss so that the QoS of internet access was categorized as satisfactory. It is hoped that from this research the company will be able to save on internet access expenses by maximizing a small bandwidth without having to increase the existing bandwidth.